FACTORS AND SPECIFIC ASPECTS OF PROVIDING NATIONAL SECURITY IN THE FIELD OF INFORMATION (Academia Science Repository, 2023)
This article describes concepts such as information security, information security, the importance of information security, areas and types of information protection. The modern foundations of national security in the field of information are interpreted.